School-Based Trauma-Informed Care to Increase Educational Engagement Among Zambia's Rural Girls - Anne Cohen (International Journal of School Social Work, 2025)
Despite international consensus that girls’ education delivers an unmatched boost to a low-income nation’s development goals, Zambia’s rural girls continue to face severe educational marginalization. Frequently, they also face trauma at the intersections of poverty, gender, and AIDS-related stigma. This paper highlights the impact of complex trauma on learning and the potential to contextualize and apply SAMHSA’s six principles of trauma-informed care (TIC) in Zambian schools. Zambian trauma-informed (TI) schools can foster resilience and improve educational engagement. The proposed framework can create inclusive, supportive school environments that empower marginalized girls and promote social justice.
Keywords: Trauma among Zambian rural girls; educational marginalization in Zambia; girls’ educational engagement in Zambia; school-based trauma intervention; SAMHSA’s six guiding principles of TIC.